The safety of cyclosporine and tacrolimus in pediatric nephrotic syndrome patients: a disproportionate analysis based on the FAERS database - Liu, Yu; Yan, Chong; Zhao, Yaowang; Deng, Sui; Zu, Jiancheng (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to systematically evaluate the safety of cyclosporine (CsA) and tacrolimus (TAC) in pediatric nephrotic syndrome (NS) patients using real-world data from the FDA Adverse Event Reporting System (FAERS).MethodsWe analyzed adverse event (AE) reports from the FAERS database between Q4 2003 and Q2 2024, focusing on AEs associated with CsA and TAC in NS patients aged 18 years and younger. We employed three signal detection methods—Proportional Reporting Ratio (PRR), Relative Reporting Ratio (RRR), and Reporting Odds Ratio (ROR)—to assess the risk of drug-related AEs. Sensitivity analyses were conducted to explore the influence of gender on AE occurrence.ResultsA total of 207 CsA-related and 145 TAC-related AE reports were included. CsA was significantly associated with nephropathy toxic (ROR = 8.26, 95% CI: 4.21–16.20), urine output decreased (ROR = 29.93, 95% CI: 3.66–244.61), and posterior reversible encephalopathy syndrome (ROR = 6.70, 95% CI: 3.17–14.14). TAC was associated with an increased risk of dystonia (ROR = 67.93, 95% CI: 8.63–534.86), kidney fibrosis (ROR = 22.65, 95% CI: 8.16–62.87), and diabetic ketoacidosis (ROR = 46.51, 95% CI: 5.68–380.97). Sensitivity analysis indicated that gender influenced the occurrence of AEs, with CsA showing higher nephrotoxicity in male patients, while TAC was more strongly associated with metabolic disorders and neurological AEs in female patients.ConclusionIn pediatric NS patients, CsA primarily induces nephrotoxicity and neurological complications, whereas TAC is more likely to cause kidney fibrosis and metabolic disorders. Enhanced monitoring of these AEs and individualized drug adjustments based on patient characteristics are recommended to optimize treatment outcomes and reduce AE incidence.